Outcome after liver resection for primary and recurrent intrahepatic cholangiocarcinoma - Nickkholgh, Arash; Ghamarnejad, Omid; Khajeh, Elias; Tinoush, Parham; Bruckner, Thomas; Kulu, Yakup; Mieth, Markus; Goeppert, Benjamin; Rössler, Stephanie; Weiss, Karl Heinz; Hoffmann, Katrin; Büchler, Markus W.; et al. (BJS open, 2019)
Background Liver resection is the only curative therapeutic option for intrahepatic cholangiocarcinoma (ICC), but the approach to recurrent ICC is controversial. This study analysed the outcome of liver resection in patients with recurrent ICC. Methods Demographic, radiological, clinical, operative, surgical pathological and follow-up data for all patients with a final surgical pathological diagnosis of ICC treated in a tertiary referral centre between 2001 and 2015 were collected retrospectively and analysed. Results A total of 190 patients had liver resection for primary ICC. The 1-, 3- and 5-year overall survival (OS) rates were 74·8, 56·6 and 37·9 per cent respectively. Independent determinants of OS were age 65 years or above (hazard ratio (HR) 2·18, 95 per cent c.i. 1·18 to 4·0; P = 0·012), median tumour diameter 5 cm or greater (HR 2·87, 1·37 to 6·00; P = 0·005), preoperative biliary drainage (HR 2·65, 1·13 to 6·20; P = 0·025) and local R1-2 status (HR 1·90, 1·02 to 3·53; P = 0·043). Recurrence was documented in 87 patients (45·8 per cent). The mean(s.d.) survival time after recurrence was 16(17) months. Independent determinants of recurrence were median tumour diameter 5 cm or more (HR 1·71, 1·09 to 2·68; P = 0·020), high-grade (G3-4) tumour (HR 1·63, 1·04 to 2·55; P = 0·034) and local R1 status (HR 1·70, 1·09 to 2·65; P = 0·020). Repeat resection with curative intent was performed in 25 patients for recurrent ICC, achieving a mean survival of 25 (95 per cent c.i. 16 to 34) months after the diagnosis of recurrence. Patients deemed to have unresectable disease after recurrence received chemotherapy or chemoradiotherapy alone, and had significantly poorer survival. Conclusion Patients with recurrent ICC may benefit from repeat surgical resection.
Gesehen am 13.11.2020